A two‐dimensional organic–inorganic lead iodide perovskite: poly[bis(3‐fluorocyclobutylammonium) [di‐μ‐iodido‐diiodidoplumbate(VI)]]. Issue 12 (25th November 2020) - Huang, Chao-Ran; Li, Peng-Fei; Luo, Xu-Zhong
Abstract : Bis(3‐fluorocyclobutylammonium) tetraiodidoplumbate(VI) is a two‐dimensional lead iodide perovskite with an experimental band gap E g of 2.44 eV. Abstract : In recent years, great technological advances have been achieved in the growth of hybrid organic–inorganic perovskites (HOIPs) and these have attracted extensive attention due to their optoelectronic properties, structural tunability and stability. We present here a new two‐dimensional hybrid organic–inorganic perovskite, namely, poly[bis(3‐fluorocyclobutylammonium) [di‐μ‐iodido‐diiodidoplumbate(VI)]], (C4 H9 FN)2 [PbI4 ] n, showing a two‐dimensional reticular layer with the organic cations in the middle of the meshes. The calculated experimental band gap is 2.44 eV and the band gap is calculated as 2.20 eV theoretically, which further suggests the potential of this compound as a semiconductor.